OPTIMALISASI PEMANFAATAN PANGKALAN PENDARATAN IKAN (PPI) BEBA GALESONG UTARA KABUPATEN TAKALAR SULAWESI SELATAN - Asmiati Salim; Danial Danial; Ihsan Ihsan (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2018)
Optimization of utilization in Beba Galesong Utara fishing port, Takalar Regency. Asmiati Salim, Marine and fisheries office of Sulawesi Selatan Province. Under supervision of Danial and Ihsan. It is important to have appropriate facility in order to support Fishing Port working progress in Bebu Galesong Utara fishing port. Incapacity one of the facility could obstruct the activity in that particular location. This problem frequently found in many fishing port in Indonesia. Beba Fishing Port is one of 23 Fishing port which contribute to original local government revenue in Sulawesi Selatan. The aim of this study is to analyze Beba fishing Port Facility for its development and optimizing under utilization facility. Methods used in this study includes various survey methods to gather fact and indication to find factual information about institution, social, economy, and politics in Beba Fishing Port. Descriptive analysis used in identifying towards existing facility and activity includes renumeration on fish auction facility, port and shipping pools. The result show, based on thirteen existing port activity included in Minesterial Decree No. 08/MEN/2012 regarding Fishing Port Affairs. Conclusion of the study shows that Facility in Beba Fishing Port in underutilization